PENGEMBANGAN E-LKPD MENGGUNAKAN PLATFORM WIZER.ME PADA BAHAN POTONGAN SAYURAN UNTUK MAHASISWA KULINER VOKASIONAL FASE E - Nurjannatin, Rizke Tajrin; Handajani, Sri; Widagdo, Andika Kuncoro; Purwidiani, Niken (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study aims to determine the feasibility of the media and content of the E-LKPD using the Wizer.me platform on the topic of vegetable cuts for the Culinary Vocational School Phase E, and student’s responses to the use of the E-LKPD. The research method applied is Research and Development (R&D) using the ADDIE model. The research subjects were 32 students of 10th Grade Culinary Program at SMKN 1 Dlanggu. The instruments used included media validation, content validation, and student response questionnaires, analyzed using percentage descriptions and mean scores. The result of this research is an E-LKPD accessible at: wizer.me/learn/83AVYU. The media feasibility received a score of 84%, and the content received a score of 82%, both of which are interpreted as "Highly Feasible." Student responses obtained a score of 89%, falling into the "Very Good" category. Therefore, the E-LKPD is deemed suitable for use in the learning process.